Ocular hypertension after silicone oil filling surgery for high myopia: a case-control study - Xiaodan Lin; Shenghui Feng; Chunmei Chen; Yadan Xiong; Na Li; Ling Tong (BMC Surgery)
Abstract Purpose This study aims to examine the correlation between specific clinical parameters, such as axial eye length, and the onset of ocular hypertension “OH” following the use of silicone oil filling in patients with high myopia. Method In this retrospective analysis, we reviewed 214 eyes from 432 patients diagnosed with severe myopia, all of whom underwent vitrectomy and were treated with silicone oil filling. The study aimed to document the incidence and timing of postoperative ocular hypertension “OH” while assessing various factors, including demographic details, medical history, additional surgical interventions, and findings from supplementary examinations (such as axial length, silicone oil emulsification, and anterior chamber penetration). Binary logistic regression was employed as the primary statistical method to identify significant predictors and their relationship with “OH”. This approach allowed for a comprehensive analysis of the impact of the duration of silicone oil presence in the eye on “OH” occurrence, providing a detailed understanding of the factors influencing post-surgical outcomes. Result The study revealed a statistically significant increase in postoperative axial length (29.21 ± 0.85 mm) compared to the preoperative length (28.31 ± 0.82 mm), corresponding to an incidence rate of 37.38% (80 cases) for “OH”. Logistic regression analysis identified the following variables as significantly associated with an increased risk of “OH” post-silicone oil filling: scleral buckling, aphakic status, silicone oil emulsification, and silicone oil penetration into the anterior chamber. The odds ratios (OR) for these variables were 1.397, 0.672, 1.859, and 1.364, respectively, indicating their predictive value for “OH” risk. Conclusion The development of “OH” post-silicone oil filling is strongly correlated with changes in the anterior segment anatomy and the dynamics of aqueous humor flow, particularly in eyes without the natural lens. Recognizing these risk factors highlights the importance of thorough preoperative evaluation and individualized postoperative care to reduce the incidence of OH in patients with high myopia, thereby improving surgical outcomes.